The Effect of Company Size, Profitability, Liquidity and Sales Stability on the Capital Structure of the Food and Beverage Subsectors Manufacturing Companies Listed on the Indonesia Stock Exchange in 2014-2019 - Velicia Velicia; Chintya Chintya; Kelvin William (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study was to determine the effect of company size, profitability, liquidity and sales stability on the capital structure of the Food and Beverage Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange in 2014-2019. This study uses a quantitative research approach. The data collection technique is literature study. The population of this research is 25 manufacturing companies in the Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange in 2014-2019. The research sample was 12 companies. The model is with multiple linear regression. The result is that company size has no effect on the capital structure of the Food and Beverage Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange in 2014-2019.